2017
DOI: 10.1016/s1470-2045(16)30627-1
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haemopoiesis and therapy-related myeloid malignancies in elderly patients: a proof-of-concept, case-control study

Abstract: Moffitt Cancer Center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
204
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(231 citation statements)
references
References 27 publications
14
204
1
1
Order By: Relevance
“…13 However, recent evidence from our studies and others has revealed that t-MN driver mutations preexist as CHIP before patients are exposed to chemotherapy/radiation therapy. [4][5][6] The current data provide additional evidence that t-MN-associated CNAs can also preexist as CHIP. In 1 patient (UID984) who did not have a detectable point mutations in known leukemia driver genes in the t-MN sample, CNAs were the only abnormalities detected as CHIP.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…13 However, recent evidence from our studies and others has revealed that t-MN driver mutations preexist as CHIP before patients are exposed to chemotherapy/radiation therapy. [4][5][6] The current data provide additional evidence that t-MN-associated CNAs can also preexist as CHIP. In 1 patient (UID984) who did not have a detectable point mutations in known leukemia driver genes in the t-MN sample, CNAs were the only abnormalities detected as CHIP.…”
Section: Discussionmentioning
confidence: 52%
“…[4][5][6] We showed that CHIP can be detected in 70% of patients with cancer who subsequently developed t-MNs and that CHIP is an independent risk factor for t-MNs. 4 Chromosome-arm level structural variations (SVs) or copy number alterations (CNAs) have also been reported as clonal mosaicism in the blood of healthy adults, and detection of these abnormalities has been linked to an increased risk of hematologic malignancy.…”
Section: Introductionmentioning
confidence: 90%
“…One murine model of TET2-deficient clonal hematopoiesis implicates macrophage TET2 deficiency in accelerated atherogenesis and CVD, 16,44 whereas another recent case control analysis revealed higher rates of atherosclerotic heart disease associated with mutations in DNMT3A, TET2, ASXL1, and JAK2 among CHIP patients. 15 Although clonal hematopoiesis does not always result in a clinical presentation of MDS, 8,11,12 our data showing a steadily increasing incidence of cardiovascular and cerebrovascular events from the time of MDS diagnosis may suggest a common underlying pathophysiology. Although the SEER database does not contain comprehensive molecular data, we noted that among patients with RARS, which is enriched for SF3B1 mutations and characterized by slower rates of progression, the proportion of deaths attributed to MDS was relatively steady with time, whereas the proportion of deaths attributed to CVD increased as patients lived longer from their time of diagnosis.…”
Section: Cumulative Incidence (%)mentioning
confidence: 77%
“…This association has been characterized as clonal hematopoiesis of indeterminate potential (CHIP). [8][9][10] Patients with CHIP have an increased risk of developing a hematologic malignancy (rate of progression 0.5-1%/year), [11][12][13][14] but they also have an increased risk of fatal cardiovascular events and all-cause mortality for unclear reasons. 13 CHIP patients appear to specifically have an increased risk of atherosclerotic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CHIP mutations are primarily found in elderly (otherwise) healthy individuals. Therefore, CHIP has also been termed age-related clonal hematopoiesis [15-19, 42-44]. …”
Section: Clonal Hematopoiesis Of Indeterminate (Clinical) Potentialmentioning
confidence: 99%